2012
DOI: 10.1108/01437721211234156
|View full text |Cite
|
Sign up to set email alerts
|

Does it pay to be productive? The case of age groups

Abstract: Using longitudinal matched employer-employee data for the period 1999-2006, we investigate the relationship between age, wage and productivity in the Belgian private sector. More precisely, we examine how changes in the proportions of young (16-29 years), middle-aged (30-49 years) and older (more than 49 years) workers affect the productivity of firms and test for the presence of productivity-wage gaps. Results (robust to various potential econometric issues, including unobserved firm heterogeneity, endogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…In contrast, firm profitability is found to depend negatively on age diversity. According to Cataldi, Kampelmann, and Rycx (), older (younger) workers tend to be “overpaid” (“underpaid”) in Belgian private sector firms. Hence, the negative effect of age diversity on profitability is likely to derive from the fact that: (1) increases in age diversity are essentially the consequence of an aging workforce, and (2) the “overpayment” of older workers may outweigh the “underpayment” of younger workers (as suggested by Cataldi, Kampelmann, and Rycx ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, firm profitability is found to depend negatively on age diversity. According to Cataldi, Kampelmann, and Rycx (), older (younger) workers tend to be “overpaid” (“underpaid”) in Belgian private sector firms. Hence, the negative effect of age diversity on profitability is likely to derive from the fact that: (1) increases in age diversity are essentially the consequence of an aging workforce, and (2) the “overpayment” of older workers may outweigh the “underpayment” of younger workers (as suggested by Cataldi, Kampelmann, and Rycx ).…”
Section: Discussionmentioning
confidence: 99%
“…This technique was pioneered by Hellerstein and Neumark () and refined by Hellerstein, Neumark, and Troske (); Hellerstein and Neumark (); Aubert and Crépon (); and van Ours and Stoeldraijer (). It is now standard in the literature on the productivity and wage effects of labor heterogeneity (see, e.g., Cataldi, Kampelmann, and Rycx ; Göbel and Zwick ; Vandenberghe ).…”
Section: Methodsmentioning
confidence: 99%
“…Concerning empirical evidence, some studies find a wage-productivity gap for older workers (e.g. Dostie, 2006, Cataldi et al, 2011 where others report no evidence for older employees' productivity lagging behind wages (e.g. van…”
Section: Introductionmentioning
confidence: 99%
“…Age is another individuallevel variable that has been linked to productivity-wage gaps in Belgium. Various studies have shown that older workers tend to be 'over-paid' (at given productivity) with respect to their younger co-workers (Cataldi, Kampelmann, & Rycx, 2012;Lallemand & Rycx, 2009;Vandenberghe, 2011Vandenberghe, , 2013.…”
Section: Characteristics Of Workers and Jobsmentioning
confidence: 99%